Structural and Functional Analysis of a Novel Psychrophilic β-mannanase from Glaciozyma antarctica PI12 - Parvizpour, Sepideh; Razmara, Jafar; Aizi Nor Mazila, Ramli; Rosli Md, Illias; Mohd Shahir, Shamsir (Springer, 2014)
The structure of a novel psychrophilic b-mannanase enzyme from Glaciozyma antarctica PI12 yeast has been modelled and analysed in detail. To our knowledge, this is the first attempt to model a psychrophilic b-mannanase from yeast. To this end, a 3D structure of the enzyme was first predicted using a threading method because of the low sequence identity (\30 %) using MODELLER9v12 and simulated using GROMACS at varying low temperatures for structure refinement. Comparisons with mesophilic and thermophilic mannanases revealed that the psychrophilic mannanase contains longer loops and shorter helices, increases in the number of aromatic and hydrophobic residues, reductions in the number of hydrogen bonds and salt bridges and numerous amino acid substitutions on the surface that increased the flexibility and its efficiency for catalytic reactions at low temperatures.